American sutra : a story of faith and freedom in the Second World War - Williams, Duncan Ryūken, 1969- (The Belknap Press of Harvard University Press, 2019)
On December 7, 1941, as the bombs fell on Pearl Harbor, the first person detained was the leader of the Nishi Hongwanji Buddhist sect in Hawai'i. Nearly all Japanese Americans were subject to accusations of disloyalty, but Buddhists aroused particular suspicion. From the White House to the local town council, many believed that Buddhism was incompatible with American values. Intelligence agencies targeted the Buddhist community, and Buddhist priests were deemed a threat to national security.In this pathbreaking account, based on personal accounts and extensive research in untapped archives, Duncan Ryūken Williams reveals how, even as they were stripped of their homes and imprisoned in camps, Japanese American Buddhists launched one of the most inspiring defenses of religious freedom in our nation's history, insisting that they could be both Buddhist and American